In search of FDI-led growth in developing countries - Stephan Klasen; Dierk Herzer; Felicitas Nowak-Lehmann D. (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
This paper challenges the widespread belief that FDI generally has a positive impact on economic growth in developing countries. It addresses the limitations of the existing literature and re-examines the FDI-led growth hypothesis for 28 developing countries using cointegration techniques on a country-by-country basis. The paper finds that in the vast majority of countries FDI has no statistically significant long-run impact on growth. In very few cases, FDI indeed contributes to economic growth both in the long and the short run. But for some countries, there is also evidence of growth-limiting effects of FDI in the short or long term. Furthermore, our results indicate that there is no clear association between the growth impact of FDI and the level of per capita income, the level of education, the degree of openness, and the level of financial market development in developing countries.
Keywords: C22; F43; 330; FDI; Growth; Developing countries; Cointegration